Multivalent Peptide–Nanoparticle Conjugates for Influenza‐Virus Inhibition - Lauster, Daniel (Angew Chem Int Ed Engl, 2017)
To inhibit binding of the influenza A virus to the host cell glycocalyx, we generate multivalent peptide–polymer nanoparticles binding with nanomolar affinity to the virus via its spike protein hemagglutinin. The chosen dendritic polyglycerol scaffolds are highly biocompatible and well suited for a multivalent presentation. We could demonstrate in vitro that by increasing the size of the polymer scaffold and adjusting the peptide density, viral infection is drastically reduced. Such a peptide–polymer conjugate qualified also in an in vivo infection scenario. With this study we introduce the first non‐carbohydrate‐based, covalently linked, multivalent virus inhibitor in the nano‐ to picomolar range by ensuring low peptide‐ligand density on a larger dendritic scaffold.